One size does not fit all: Variation in anatomical traits associated with emersion behavior in mudskippers (Gobiidae: Oxudercinae) - Corush, Joel B.; Zhang, Jie (Frontiers in Ecology and Evolution, 2022)
Life histories involving transitions between differing habitats (i.e., aquatic to terrestrial or marine to freshwater) require numerous anatomical, physiological, and behavioral changes. Often the traits associated with these changes are thought to come in suites, but all traits thought to be associated with particular life histories may not be required. While some traits are found in all species, a grab bag approach may apply to other traits in that any trait may be sufficient for successful habitat transitions. We examine patterns of morphological traits associated with prolonged emersion in mudskipper, an amphibious fishes clade, where prolonged emersion appears twice. We test the evolutionary history of multiple characteristics associated with cutaneous respiration. We find most traits thought to be key for prolonged emersion show no phylogenetic signal and no tight correlation with prolonged emersion. Such traits appear in species with prolonged emersion but also non-emerging species. Only capillary density, which, when increased, allows for increased oxygen absorption, show strong phylogenetic signal and correlation with prolonged emersion. Further experimental, functional genomics, and observational studies are needed to fully understand the mechanisms associated with each of these traits. With respect to traits associated with other particular behavior, a comparative framework can be helpful in identifying evolutionary correlates.